1984
DOI: 10.1016/0014-5793(84)80599-2
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of seed reserve proteins

Abstract: Two types of storage pathways are proposed for the synthesis and compartmentalization of seed reserve globulins and prolamins. A discussion of the regulatory mechanisms in reserve protein topogenesis reveals that certain factors such as solubility characteristics of the protein molecule and/or specific sorting sequences may underline the discrimination in deposition of globulins and prolamins. Finally, a hypothetical relationship between the type of storage pathway and the seed protein concentration is briefly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In any event, the different patterns of synthesis of PAPI, CI-1, and ASI make them model candidates for processing studies in aleurone cells. Studies on the intracellular deposition and/or secretion of these proteins might clarify the purported differences between endosperm and aleurone protein bodies (1,8,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any event, the different patterns of synthesis of PAPI, CI-1, and ASI make them model candidates for processing studies in aleurone cells. Studies on the intracellular deposition and/or secretion of these proteins might clarify the purported differences between endosperm and aleurone protein bodies (1,8,28).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopic studies have shown that the ultrastructure of protein bodies found in aleurone cells is different from those of starchy endosperm cells (for reviews see Refs. 1,28). Such differences imply differential expression during seed development of genes encoding various seed proteins in these two ontogenically closely related tissues.…”
mentioning
confidence: 99%
“…All six datasets feature the characteristic starch metabolism, biosynthesis, and storage proteins. The content is affected by the starch preparation method used, as seed proteins have varying solubilities [ 37 ] and, as such, are divided into four solubility classes (the Osborne fractions): water-soluble albumins, water-insoluble globulins, alcohol-soluble gliadins, and insoluble glutenins [ 38 ]. As the first step of each method used imbibed and wet-ground rice, the albumins were solubilized and discarded early in the starch granule preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, plant biotechnology takes advantage of the storage and delivery properties of proteins bodies by using specific promoters to target cytokines, vaccine candidates, growth hormones and other biopharmaceuticals to the seed endosperm, a natural protein deposition site (Adeli & Altosaar, 1984;Wright et al, 2001;Sardana et al, 2002). In this study, we explored the accumulation of rhCD14 protein in transgenic tobacco seeds.…”
Section: Introductionmentioning
confidence: 97%